2016
DOI: 10.1097/tp.0000000000001399
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Diabetes After Liver Transplantation

Abstract: Glycemic control was inadequate in 33.3% of LT recipients with diabetes, and screening protocols for diabetes-associated conditions did not meet the standards for medical care set by the American Diabetes Association in any of the participating centers. Consequently, this study reveals a clear deficiency in the quality of diabetes care provided to patients after LT and, hence, we predict that future progress in this area will have a significant impact on medium-term to long-term outcome of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Another important finding of this study is that all the CV risk factors assessed, except tobacco use, showed a continuous increase during the follow‐up that is evident since the first 6 months after LT. Notably, in accordance with other reports, the control of diabetes, dyslipidemia, and arterial hypertension worsened during the 5 years after LT . Despite the relatively short follow‐up of this series that may not allow us to fully capture the longterm impact of the new‐onset CV risk factors on late CV morbidity, this study revealed that the development of new‐onset CV risk factors may modify the CV risk in the first 5 years after transplantation.…”
Section: Discussionsupporting
confidence: 85%
“…Another important finding of this study is that all the CV risk factors assessed, except tobacco use, showed a continuous increase during the follow‐up that is evident since the first 6 months after LT. Notably, in accordance with other reports, the control of diabetes, dyslipidemia, and arterial hypertension worsened during the 5 years after LT . Despite the relatively short follow‐up of this series that may not allow us to fully capture the longterm impact of the new‐onset CV risk factors on late CV morbidity, this study revealed that the development of new‐onset CV risk factors may modify the CV risk in the first 5 years after transplantation.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to the previously mentioned outcomes, PTDM has also been associated with higher insulin use in post-LT patients. A cross-sectional study by Alvarez-Sotomayor et al[ 24 ] evaluated 344 patients of whom 141 patients experienced PTDM (157 total but 16 patients did not have HbA1c readings prior to enrollment). Patients with PTDM who had adequate glycemic control (defined as HbA1c < 7%), were significantly less dependent on insulin (39.4%) compared to patients with inadequate glycemic control (80.8%) (OR 6.6, 95%CI: 1.8-24.6, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A reasonable target, based on our findings would be a range between 120 mg/dL to 150 mg/dL, given that BG ≥ 150 mg/dL were associated with negative post-LT outcomes. In addition, interventions through nurse-initiated glucose management protocols to achieve specific target BG levels, early screening to identify patients at high-risk for PTDM, and use of oral agents for management of PTDM seem to be a promising approaches to minimize post-LT outcomes[ 17 , 22 , 24 ]. Although not discussed extensively in this review, optimizing immunosuppression regimens may also play an important role as noted by the potential association between basiliximab and pulse steroids with PTDM[ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 29 , 30 , 36 Tight glucose control, sparing using of corticosteroids, and early referrals to endocrinology should be considered to decrease the risk of NAFLD disease progression in this patient population. 19 , 37 …”
Section: Risk Factors For Nafld In Allograftmentioning
confidence: 99%